A subcellular tug of war involving three MYB‐like proteins underlies a molecular antagonism in Antirrhinum flower asymmetry. (30th May 2013) - Raimundo, João; Sobral, Rómulo; Bailey, Paul; Azevedo, Herlânder; Galego, Lisete; Almeida, Jorge; Coen, Enrico; Costa, Maria Manuela R.
Summary The establishment of meristematic domains with different transcriptional activity is essential for many developmental processes. The asymmetry of the Antirrhinum majus flower is established by transcription factors with an asymmetric pattern of activity. To understand how this asymmetrical pattern is established, we studied the molecular mechanism through which the dorsal MYB protein RADIALIS (RAD) restricts the activity of the MYB transcription factor DIVARICATA (DIV) to the ventral region of the flower meristem. We show that RAD competes with DIV for binding with other MYB‐like proteins, termed DRIF1 and DRIF2 (DIV‐ and‐RAD‐interacting‐factors). DRIF1 and DIV interact to form a protein complex that binds to the DIV‐DNA consensus region, suggesting that the DRIFs act as co‐regulators of DIV transcriptional activity. In the presence of RAD, the interaction between DRIF1 and DIV bound to DNA is disrupted. Moreover, the DRIFs are sequestered in the cytoplasm by RAD, thus, preventing or reducing the formation of DRIF‐DIV heterodimers in the nuclei. Our results suggest that in the dorsal region of the Antirrhinum flower meristem the dorsal protein RAD antagonises the activity of the ventral identity protein DIV in a subcellular competition for a DRIF protein promoting the establishment of the asymmetric pattern of gene activity in the Antirrhinum flower.